Operation characteristics and testing parameters of transport channels - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2025)
Today's advanced, automated serving systems must operate efficiently in a dynamically changing environment, where modern methods and procedures can be applied during the realization of handling processes. To be able to apply various optimization methods and simulation software with appropriate efficiency during the planning and operation of material handling devices, it is necessary to explore the parameters of the technical devices to take the individual characteristics into account. In this article, the next step of previously started research is presented, in which the variants of conveyor belts and the most important operating characteristics are explored.